Coordinating REST interactions in service choreographies using blockchain - Francesco Donini; Alessandro Marcelletti; Andrea Morichetta; Andrea Polini (Blockchain: Research and Applications)
In Service Oriented Computing (SOC), different services interact and exchange information to reach specific objectives. To model interorganizational SOC systems, choreography modeling languages have emerged to represent the distributed coordination among the involved organizations. From the realization perspective, blockchain technology is emerging as a promising run-time supporting peer-to-peer communication technology without the need for a central coordinator, thanks to its intrinsic security, trust, and decentralization characteristics. However, while blockchain can bring many advantages, technological barriers still limit its adoption in organizations, due to the costly and time-consuming learning process. For this reason, we propose RESTChain, a framework that automatically enables the interactions that take place among the participants in a service choreography exploiting blockchain technology. Starting from a choreography specification, the framework provides a set of mediators and automatically generates a smart contract that coordinates the service interactions. The mediators are software components that are directly connected with the smart contracts and expose REpresentational State Transfer (REST) APIs in compliance with the role played by the organizations in the choreography. In this way, the services deployed by one organization can communicate with the services made available by another organization through the blockchain in a secure and transparent manner. The proposed approach has been implemented on the Layer 2 Polygon blockchain and validated in a market retail case study analyzing its efficiency in terms of time and cost.